Nutritional, mineral and organic acid composition of passion fruit (Passiflora species) - Ramaiya, Shiamala Devi; Bujang, Japar Sidik; Zakaria, M. Hazmadi; Saupi, Noorasmah (Elsevier, 2019)
This study focused onproximate composition, mineral content and organic acid properties of fruit juices from four Passifloraspecies; Passiflora edulis(Purple), Passiflora edulis(Frederick), Passiflora maliformis, and Passiflora quadrangularis and the mesocarp of Passiflora quadrangularis. The moisture content varied between 84.37±0.63% in P. edulis(Frederick) to 86.63±0.33% in mesocarp of P. quadrangularis. The ash content of mesocarp of P. quadrangulariswas significantly lower (0.51±0.02%) than its juice (1.37±0.14%). Among the Passiflora species, P. edulis(Purple) and P. edulis(Frederick) possessed higher protein, 2.81±0.19% and 2.40±0.11%, respectively. The fiber content in P. quadrangularis mesocarp was significantly higher (8.49±0.40%) than other juices. Passiflorafruits have fat content <0.5% in edible portion. The carbohydrate content of Passiflorafruit juices was not significantly different with ranged 6.57±0.29% in P. quadrangularisto 7.44±0.69% in P. edulis(Frederick). Additionally, a cup of 247 mL Passiflorajuices provided ~34% of potassium, 60-80% Magnesium, >80% phosphorus and provides an adequate level of micronutrients especially Ferum content which is 90% of daily recommended allowance of minerals. The major organic acid in Passiflorafruit juice was citric acid and ranged 1137.00±0.13 mg 100 g-1in P. quadrangularisto 1487.30±0.28 mg 100 g-1in P. edulis(Purple). Malic acid was second abundant organic acid with 156.00±0.07 mg 100 g-1in P. edulis(Frederick) to 502.30±0.07 mg 100 g-1in P. quadrangularis. Apart from the common species of Passiflora edulis, other lesser known Passifloraspecies are also gaining visibility in drinks, food and health promoter.